Effect of Starch and Chitosan Addition on Swelling Properties of Neutralized Poly(Acrylic Acid)-Based Superabsorbent Hydrogels Prepared by Using γ-Irradiation Technique - D. R. Barleany; H. Heriyanto; H. Alwan; V. Kurniawati; A. Muyassaroh; E Erizal (PPIKSN-BATAN, 2022)
Superabsorbent hydrogels are polymers with a 3D network that have attracted the attention of scientists and industrialists because of their fantastic ability to absorb and retain water and aqueous solutions. The most widely used and commercially available superabsorbent hydrogels are synthetic K-acrylate materials. In this novel study, superabsorbent hydrogels have been developed using natural ingredients to have more biodegradable properties. Superabsorbent hydrogels were synthesized from acrylic acid, cassava starch, and chitosan using the γ-irradiation method under different experimental conditions. The γ-irradiation technique was chosen to produce hydrogels free of residues that may remain when chemical crosslinkers are used. The effects of irradiation dose, acrylic acid composition, and the amount of cassava starch and chitosan on the characteristics of produced hydrogels were analyzed. The resulting polymers were further characterized by fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM) to evaluate the structure. The thermal behavior of superabsorbent products at different neutralization doses was tested with differential scanning calorimetry (DSC). FTIR data indicated that the grafting reaction was successfully implemented in this work. SEM analysis showed that the hydrogel produced from this study was porous and there was a reduction in pore size with the addition of starch and chitosan. It can be concluded that the addition of cassava starch and chitosan affects the acrylic acid-based superabsorbent properties, which are pore size, thermal behavior, gel content, antibacterial activity, and swelling capacity in water, salt, and urea solutions. The best hydrogel was obtained by adding 0.25 g of cassava starch and 0.25 g of chitosan, using 50 % acrylic acid neutralization and 5 kGy γ-irradiation doses. The graft polymers possess the maximum swelling capacity of 670 g/g for distilled water, 520 g/g for NaCl solution, and 767 g/g for urea solution (relative to the dry weight). These products were sterile from Escherichia coli bacteria and had the potential to be applied as superabsorbent resins for various fields.